Premalignant Lesions of the Colon - Rodger C Haggitt (Canadian Journal of Gastroenterology)
Cancer of the colon and rectum is the second most common cancer in men and women in North America. Early diagnosis results in detection of early stage tumours with a high probability of cure. Several studies document the efficacy of screening for the early detection of colorectal cancer; however, its incidence is so high chat screening the entire older adult population is not feasible. Thus, attempts have been made to focus screening on patients at higher than average risk for colorectal carcinoma; these include patients with predisposing conditions or premalignant lesions of the colon. Common predisposing conditions include previous resection of an adenoma or carcinoma, a family history of colorectal carcinoma, and ulcerative colitis of more than IO years' duration. The most important premalignant lesion is the colonic adenoma. Such lesions must be removed in their entirety and examined histologically to exclude the presence of carcinoma. Approximately 51 % of patients with colonic adenomas removed by endoscopic polypectomy will be found to have a carcinoma within the polyp. If a pedunculated adenoma containing invasive carcinoma can be removed with a clear stalk margin, the risk of nodal metastasis is very low, probably less than 2%. In contrast, sessile lesions containing carcinoma already show invasion into the submucosa of the underlying bowel wall with a significant risk of nodal metastasis. Segmental colonic resection is rarely necessary for management of the patient with carcinoma arising in a pedunculated adenoma, but it is often justified for the patient with carcinoma in a sessile lesion. Dysplasia arising in ulcerative colitis is another important premalignant lesion that can be detected by colonoscopy with biopsy. The presence of high grade dysplasia in a patient with longstanding ulcerative colitis is an indication for colectomy.